In vitro Screening of Glutathione- S -Transferase Inhibition by Different Extracts of Verbascum sinuatum - Lubna Abdallah*; Aseel Abu Hardan (Lorestan University of Medical Sciences, 2023)
Background and Aim: The concern toward using herbs as enzyme inhibitors such as glutathione-s-transferases (GSTs) may result in the improvement of proliferative diseases. Moreover, it may overcome the problem of multidrug resistance tumors. Based on that, this experiment was conducted to detect the impact of using aqueous, ethanol and methanol extracts from Verbascum sinuatum L. (Scrophulariaceae) that grow wild in Palestine as enzymatic inhibitors. Materials and Methods: The impacts of these three extracts at four studied concentrations (250, 500, 750 and 1000 µg/mL) on the activity of purified hepatic glutathione-s-transferases were estimated spectrophotometrically by using-chloro-2,4-dinitro-benzene (CDNB) as substrate. Results: The results of the present research indicated that all the three prepared extracts of V. sinuatum could inhibit the activity of GSTs at all examined concentrations. Moreover, according to the results, the alcoholic extracts from the studied plant species were more influential in the activity of GSTs than the aqueous ones. However, minor inhibitory variations were observed between methanol and ethanol extracts. It is notable that all the studied extracts manifested inhibitory effects in a dose-dependent manner. Conclusion: The results of this study emphasized the possibility of utilizing V. sinuatum extracts in pharmaceutical industry of new medications to fight drug resistant tumors in general and GST-induced tumors in particular.